Retelling the siege of Jerusalem in early modern England - Neelakanta, Vanita (The Early Modern Exchange Ser., 2019)
Intro -- Contents -- Acknowledgments -- Introduction -- Chapter 1 -- Chapter 2 -- Chapter 3 -- Chapter 4 -- Chapter 5 -- Epilogue -- Notes -- Bibliography -- Index.